Persepsi warga mengenai perilaku hidup bersih dan sehat di Dusun Kebonan, Semarang - Aprillia Vanessha Mailoa; Maria Dyah Kurniasari; Tesabela Sanfia Messakh (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Kebonan Village, Semarang Regency, Central Java is the region with the highest number of diarrhea cases. Based on the profile of Puskesmas Regency/City Semarang in 2014, there were 84 findings of diarrhea cases. The initial observation revealed that living environment in Kebonan village was not hygiene. Most of the times, the ditch loaded by garbage, the food often surrounded by flies, people often do not wash their hands after completing their daily activities, and there are houses that still have no latrines. These behaviors were not in accordance with the Clean and Healthy Behavior, thus estimated as the main cause of high cases of diarrhea in Kebonan. This situation was in opposition with Government socialization to local residents about Clean and Healthy Behavior (Perilaku Hidup Bersih dan Sehat/PHBS). Therefore, the problem identified in this research is the failure of government programs through the Department of Health in disseminating the importance of PHBs which resulting in the high number of diarrhea. The aim of this study is to describe the perception of citizens about the PHBS in Kebonan Village, Semarang. This study used the qualitative method with the descriptive design. Researcher employs primary and secondary data. Primary data collected through in-depth interviews with residents of Kebonan, while secondary data was gathered through observations. Data validity was further tested through member-checking method. The research concludes that the perception of Kebonan residents on PHBs are divided into three aspects: realizing the physical and environmental cleanliness, who is responsible for realizing PHBs, and constraints in realizing PHBS. Citizen roles to keep the environment clean, manage domestic waste, use a proper toilet, washing hand and bathing, and keeping female organ hygiene are essential in creating a good and clean living environment.